Giving Sports Burden to Behavior of Students of the Faculty of Sports Science, Universitas Negeri Medan - Fransen Sinaga; Nurkadri; Muhammad Reza Destya (East Asian Journal of Multidisciplinary Research, 2022)
This study aims to determine the provision of sports loads on the social behavior of Unimed Fiction students. The methodology in this study uses descriptive analytic which is a method that describes the relationship between the provision of sports loads and social behavior. The sample in this study used a purposive sampling technique or conditional sample where the sample selection was based on students who had a sports load in accordance with the indicators in the questionnaire. The research instrument used in this study was a questionnaire questionnaire given to a sample of unimed fiction students. The data analysis technique used SPSS Version 23 software. The results of the data analysis carried out showed the magnitude of the correlation coefficient of sports load on social behavior with a value of 0.956. The results showed that there was a relationship between the provision of sports loads on social behavior with a significant value of 0.000 sig with a significant correlation of 0.01.